Oxygen Reduction on Anthraquinone Diazonium Compound Derivatised Multi‐walled Carbon Nanotube and Graphene Based Electrodes. Issue 2 (14th September 2016) - Mooste, Marek; Kibena‐Põldsepp, Elo; Matisen, Leonard; Tammeveski, Kaido
Abstract: In this work, graphene and multi‐walled carbon nanotubes were derivatised with anthraquinone (AQ) groups using spontaneous or electrochemical grafting of Fast Red AL salt. Glassy carbon (GC) electrodes were coated with AQ‐modified carbon nanomaterials to study the oxygen reduction reaction (ORR). These nanomaterials were characterised by X‐ray photoelectron spectroscopy and multilayer formation of AQ on the electrografted electrodes was observed. All the modified electrodes showed enhanced electrocatalytic activity towards the ORR in alkaline media. High AQ loading on the electrodes was found and the number of electrons transferred per O2 molecule was between 2 and 4. In addition, the stability testing of AQ‐derivatised carbon nanomaterial‐coated GC electrodes was performed. Abstract :